Rocketship and the Rural Health Workforce Revolution in the Pacific: Growing Skilled Medical Generalists Across the “Blue Continent” - McIver, Lachlan; Manahan, Dan; Jones, Sam; 'Ulufonua, Lisiate (Frontiers in Public Health, 2021)
Dramatic shifts are occurring in rural health workforces in Pacific island countries (PICs) due to an unprecedented convergence of political agreement, policy commitment, donor support and technical assistance. In particular, the impact of ‘medical internationalism’ is being felt across the Pacific, with new doctors returning home in far greater numbers than ever before, the majority having graduated from medical schools in Cuba, China and other countries outside the region. With a vision of ‘Healthy Islands’, the main objective of expanding overseas training opportunities for Pacific island medical students has been to correct the maldistribution of the medical workforce in PICs and improve health access and quality of care in rural areas by deploying the new graduates to outer-island facilities. However, the return of these new graduates in several PICs has demonstrated that additional training is required to equip them with the knowledge and skills necessary to practise safely and sustainably in unsupervised settings. The development of specific postgraduate programmes has been urgently needed to provide pathways to vocational training and specialisation in rural medicine appropriate to the Pacific region. Rocketship Pacific Ltd (Rocketship) is an international health charity, based in Australia, dedicated to improving health in Pacific island countries through stronger primary care, with a focus on rural health workforce support. Since 2015, Rocketship has been working in partnership with the Ministries of Health and other key partners in Solomon Islands, Timor-Leste, Tonga and Vanuatu to design and deliver postgraduate training programmes in family, community and rural medicine. To date, this has resulted in new postgraduate Family Medicine courses being established in Timor-Leste and Tonga; a rural medical workforce support programme being delivered in Vanuatu; and a new Postgraduate Diploma in Rural Generalist Medicine being designed in Solomon Islands. These new programmes, as well as other notable initiatives elsewhere in the Pacific such as the Master of Medicine (Rural) programme in Papua New Guinea, the Diploma and Master of Family Medicine programme in Fiji and the Cook Islands Fellowship in General Practice, are transforming the health workforce in PICs with the potential to benefit island people across the ‘Blue Continent’.